Effect of drought disturbance in a sclerophyll forest on the micromammal community in the Río Clarillo National Park, Metropolitan Region, Chile - Susan Fletcher; Carlos Sarmiento; Gisela C. Stotz; Verónica Quirici (Revista Chilena de Historia Natural)
Abstract Background Micromammals play an important role in mediterranean ecosystems. The “megadrought” in the sclerophyll forest has caused a “browning” that implies, among other things, the reduction of canopy cover. The effects of forest browning on the taxonomic and functional diversity of micromammals were evaluated. Methods Forests with high and low disturbance degree were characterized based on the level of browning and canopy cover. To study the community of micromammals in these forests, the Capture-Mark-Recapture method was used with Sherman traps. Community indices such as Shannon–Wiener and Pielou were calculated. The Coefficient of Variation was used to study functional diversity for each trait separately. Multivariate measures FRic, FEve and FDiv were used to determine multidimensional diversity. Results We observed differences in species composition and in richness, diversity, and cover variables between forest types. However, micromammal communities were similar in taxonomic and functional diversity in highly and slightly disturbed forests. Discussion The micromammal community appears to show some resistance to forest changes due to disturbance, which could be related to their generalist diet and high dispersal capacity. The presence of the genus Rattus could entail a decrease in native rodent diversity and could have a greater effect than the disturbance of the forest due to drought. These results are an invitation to conduct long-term studies to better understand the potential vulnerability of the different micromammal species to disturbed sclerophyll forests affected by drought.